The influence of the profile, the surface treatment of wire electro samples on their cutting ability - M. G. Kiselev; A. V. Drozdov; A. V. Moskalenko; P. S. Bogdan (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article is devoted to experimental evaluation of the influence of electric-mode parameters of the original surface treatment of wire cutting tool on its surface in the process of cutting them brittle materials using free abrasive. The description of the established systems and procedures are set out questions for experimental studies. The results, reflecting the influence of the profile, the surface treatment of wire electro samples on their cutting ability are presented and analyzed.